2019
DOI: 10.1055/s-0039-1678671
|View full text |Cite
|
Sign up to set email alerts
|

Maxillofacial Injuries in Bear, Tiger, and Jackal Attacks

Abstract: Maxillofacial injuries as a result of wild animals attack are not commonly encountered and reported in the literature. Factors such as increasing human population near forest and lack of dependable physical barriers between forest and human habitations lead to frequently encountered incidents of wild animal attacks over humans especially in far western region of Nepal. The authors present two cases of bear attacks, one case of tiger attack, and one case of jackal attack and explain the pattern of maxillofacial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…77 Table-1 showed pattern of bear maul injury after review of 252 cases reported in various articles from India and Nepal due. [77][78][79][80][81][82] Bear mauling wound commonly involved the face (81-96%) and head (54.7%). Wounds by claws, paws and a combination of both due to bear attacks can present in extensive sharp and blunt injuries and may associate with underlying bone fractures.…”
Section: Ocular Injury Due To Bear Maulsmentioning
confidence: 99%
See 1 more Smart Citation
“…77 Table-1 showed pattern of bear maul injury after review of 252 cases reported in various articles from India and Nepal due. [77][78][79][80][81][82] Bear mauling wound commonly involved the face (81-96%) and head (54.7%). Wounds by claws, paws and a combination of both due to bear attacks can present in extensive sharp and blunt injuries and may associate with underlying bone fractures.…”
Section: Ocular Injury Due To Bear Maulsmentioning
confidence: 99%
“…A single dose of tetanus toxoid may be given depending on the immune status of the patient. 77,78,81,82 Wounds due to large animal bites are considered to be dirty or contaminated. Surgical toileting and debridement are an essential part of the treatment.…”
Section: Ocular Injury Due To Bear Maulsmentioning
confidence: 99%
“…Wounds from bites and claws were deep, involved neurovascular structures and tracked to the cervical spine 48 and base of the skull. 17 Except for six cases where paws or claws were the main inflictor, 9,10,18,22,25,31 bites were the primary vehicle of injury. Bite wounds were paired 17,36,43,44,48 consisting of two to four wounds separated in space generating large oval injuries at the skin with diameters of 2-3 cm, 17,35,48 and depths up to 7 cm, 44 with a surrounding soft tissue crush injury.…”
Section: Pooled Injury Pattern Of All Cats: Wound Morphology and Frac...mentioning
confidence: 99%
“…44,48 Paediatric and captivity analysis Paediatric injury patterns did not differ from adults, with primary head or neck injury remaining the dominant injury form in 78% of victims. 10,21,22,25,27,29,30 The sole paediatric fatality was due to polytrauma from a leopard in a 2-year-old female with major skull and neck wounds. 29 Head and neck also remained the most injured region irrespective of location or captivity (wild 56%, captive 73%).…”
Section: Pooled Injury Pattern Of All Cats: Wound Morphology and Frac...mentioning
confidence: 99%
See 1 more Smart Citation